2018
DOI: 10.2147/ijn.s153701
|View full text |Cite
|
Sign up to set email alerts
|

Cellular interaction of a layer-by-layer based drug delivery system depending on material properties and cell types

Abstract: BackgroundDrug delivery systems (DDS) and their interaction with cells are a controversial topic in the development of therapeutic concepts and approaches. On one hand, DDS are very useful for protected and targeted transport of defined dosages of active agents. On the other hand, their physicochemical properties such as material, size, shape, charge, or stiffness have a huge impact on cellular uptake and intracellular processing. Additionally, even identical DDS can undergo a completely diverse interaction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Thereafter incubation with microcarriers was carried out for 16 h and at a micocarrier:cell ratio of 2:1. This time frame allowed for an optimal uptake and processing rate as revealed by our previous study, where uptake in different cell lines was shown to be completed at around 5–6 h [ 13 ]. While uptake for both, polymer and SLB microcarriers, progresses without loss of layer components, subsequent processing refers to passage of the endosomal-lysosomal compartment and the beginning of the disassembly of the lipid bilayer and polymer multilayer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thereafter incubation with microcarriers was carried out for 16 h and at a micocarrier:cell ratio of 2:1. This time frame allowed for an optimal uptake and processing rate as revealed by our previous study, where uptake in different cell lines was shown to be completed at around 5–6 h [ 13 ]. While uptake for both, polymer and SLB microcarriers, progresses without loss of layer components, subsequent processing refers to passage of the endosomal-lysosomal compartment and the beginning of the disassembly of the lipid bilayer and polymer multilayer.…”
Section: Resultsmentioning
confidence: 99%
“…It is known, that cytoskeletal elements can naturally induce mechanical stress on the nucleus leading to nucleus confinement and deformation [ 36 ], an effect which is cell type dependent [ 37 ]. Additionally, mechanical deformation by externally added elements, such as functionalized microcarriers, seem not to lead to nucleus irritations, as no signs of apoptosis or necrosis could be found [ 13 ]. Thus, this system could then be adapted to transport active agents near the nucleus for specific applications, such as for nucleus-targeting cancer therapeutics [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been shown that microcapsules can be taken up by various cell types [ 45 ]. The uptake efficiency of microcapsules may depend on their size [ 46 ], charge of the outer layer [ 47 ], the type of polyelectrolytes used [ 48 ], the elasticity or deformability of the microcapsule shell [ 49 ] or their shape [ 50 ]. Here, human mesenchymal stem cells were used to analyse the endocytosis of nanoceria-loaded microcapsules using fluorescence microscopy ( Figure 3 a).…”
Section: Resultsmentioning
confidence: 99%